Gender Alert: Women and Girls of Sudan - Fortitude Amid the Flame of War - United Nations Women (United Nations, 2024)
This publication provides a detailed analysis of the ongoing humanitarian crisis in Sudan, focusing on its disproportionate impact on women and girls. As the country faces the largest internal displacement since the Syrian civil war, millions of Sudanese, particularly women and children, are grappling with severe challenges. This report highlights key data on displacement, malnutrition, lack of access to healthcare, gender-based violence, and food insecurity. It also explores how deeply entrenched gender inequality exacerbates the vulnerabilities of female-headed households and the critical barriers women face in accessing essential resources. It also offers a comprehensive overview of the socio-economic and health impacts on women and girls, drawing from recent assessments and data. The report emphasizes the need for targeted humanitarian interventions. We consider it as an essential resource for understanding the gender dimensions of Sudan’s humanitarian crisis and calls for focused action to mitigate its effects.